A systematic review of volcanology learning and teaching in higher education - Dohaney, Jacqueline; Jolley, Alison; Kennedy, Ben; Watson, Alexander (Volcanica, 2023)
We present a systematic map of the volcanology higher education literature (1983–2020) consisting of 47 peer-reviewed full texts. The literature describes curricula in varied formats and settings, namely: simulated, in-person, and field-based learning. The phenomena that students are learning about commonly include volcanic processes and landforms, applicable to learning within various geoscience subdisciplines. Frequently published research includes volcano misconceptions and simulated eruptions. However, most texts focus on practitioner wisdom and lack research information, empirical evidence, and/or a research-oriented methodology. A lack of research orientation is a documented phenomenon within the broader field of geoscience education, which is young compared to other discipline-based education research fields. Based on our findings, we recommend future research in conceptual learning of volcanology, instructional strategies, volcanology and society interactions, volcanology education equity and inclusion, volcanology cognition, quantitative learning, affective learning, and institutional change in volcanology.